THE RELATIONSHIP BETWEEN SPIRITUAL WELL-BEING AND THE RISK OF DEPRESSION IN THE ELDERLY AT THE TRESNA WERDHA SOCIAL CARE HOME IN EAST JAKARTA - Adeline Adeline; Lucia Utami; Jesika Pasaribu (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: The physical decline of elderly people often causes them to experience loneliness, hopelessness, and feelings of vulnerability, which can contribute anxiety or depression. The level of spiritual well-being plays a significant role in enhancing the mental health of the elderly. Key strategies to improve the mental health of the elderly include religious activities such as attending religious services, receiving sacraments, private prayer, reading holy books, meditation, scripture study, religious retreats, and other religious activities. Purpose: The purpose of this study was to determine the relationship between spiritual well-being and the risk of depression in the elderly. Methods: The research is quantitative descriptive correlation method using a cross-sectional approach. The sample in the study consisted of 106 elderly people. Data analysis was performed using the Chi-square test Results: The results showed a correlation between spiritual well-being and the risk of depression among elderly residents at the Tresna Werdha Social Welfare Institution in East Jakarta, with a p-value of 0.000 (p<0.05). Conclusion: The level of spiritual wellbeing in older adults has an influence on the risk of depression in older adults. Older adults who have high spiritual well-being have better coping mechanisms and this has a positive impact on health and can reduce the risk of depression that may experience.